(untitled) (Future Cities and Environment, 2021)
Biomass-based aerogel is a new promising environmentally friendly filter material to remove fine particle matter and minimize air pollution. This study aims to investigate the air filtration properties of biomassbased aerogels via tests in a transparent chamber and verification in a real room with a burning smudge stick as a the particle source. The biomass-based aerogel used in this study is made of polysaccharides, protein and waste agricultural by-product (wheat straw). The addition of wheat straw contributes to the increase of surface area and complexity of the biomass-based aerogel pore structure. Compared with other commonly used commercial filtration materials including high-efficiency particulate air (HEPA) filter, surgical mask, regular cloth and silica aerogel, biomass-based aerogel K0.9G1.8S3.6WS1.8 shows excellent performance to remove PM 2.5 (99.50%) and PM 10 (99.40%) from the environment. When using the biomass-based aerogel, the filter core sample has a smaller volume and simpler structure than HEPA to achieve the similar filtration performance. The filtration performance of the biomass-based aerogels has been verified with a real room test. The current work demonstrates the high potential of biomass-based aerogels for infiltration application in different fields and provides an avenue to reuse agricultural byproducts.